Strategies used by Rural Secondary School Governing Bodies to Enhance the Quality of Education - Tomose, Zimisele Raymond; Mavuso, Mzuyanda Percival; Olawumi, Kayode Babatunde (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study explored the strategies employed by School Governing Bodies (SGBs) to enhance the quality of education in three selected secondary schools in the Eastern Cape Province, South Africa. Despite some improvement in Grade 12 results within the province, a downward trend was observed until 2016, raising concerns given that SGBs are legally mandated to improve educational quality. This qualitative research employed semi-structured interviews to gather data from twenty-two participants, including eighteen SGB members, two school principals, and two Education Development Officers (EDOs). The study applied Governance Theory as a framework to investigate the strategies used by SGBs to promote educational quality in their schools. The findings revealed that while SGB members were often inadequately trained for their governance roles, some employed strategies such as goal-sharing, fostering a common purpose, and engaging the community to improve education. However, the study also highlighted divergent views, with some participants questioning whether SGBs had any concrete strategies to enhance educational quality. Based on these findings, the study recommends the development of clear guidelines to assist SGBs in formulating effective strategies to improve the quality of education in schools. This paper will contribute to the body of existing knowledge, practice, and policy development to enhance the performance of the SGB to enhance the quality of education in South Africa.